2010
DOI: 10.1007/s10533-010-9534-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil frost on the quality of dissolved organic carbon in a boreal forest soil: combining field and laboratory experiments

Abstract: Riparian soils exert a major control on stream water dissolved organic carbon (DOC) in northern latitudes. As the winter climate in northern regions is predicted to be particularly affected by climate change, we tested the sensitivity of DOC formation to winter conditions in riparian soils using an 8 year field-scale soil frost manipulation experiment in northern Sweden. In conjunction with the field experiment, we also carried out a laboratory experiment based on three levels of four winter climatic factors: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 62 publications
(65 reference statements)
1
30
2
Order By: Relevance
“…Based on these values, it appears probable that direct frost damage is responsible for the observed shifts in species occurrences. Besides the direct lethal eVects of frost, the sub-lethal eVects of freezing could also be of high ecological importance, and the period of freezing, the number of freeze thaw cycles and the rate of freezing can all increase the size of the eVect for a given freezing intensity (Vestgarden and Austnes 2009;Haei et al 2011). Furthermore, the role of biotic (e.g., mycorrhizal interactions) as well as abiotic interactions (e.g., soil moisture at the point of freezing determining the importance of physical stress on plant roots) deserves further investigation (Kreyling 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these values, it appears probable that direct frost damage is responsible for the observed shifts in species occurrences. Besides the direct lethal eVects of frost, the sub-lethal eVects of freezing could also be of high ecological importance, and the period of freezing, the number of freeze thaw cycles and the rate of freezing can all increase the size of the eVect for a given freezing intensity (Vestgarden and Austnes 2009;Haei et al 2011). Furthermore, the role of biotic (e.g., mycorrhizal interactions) as well as abiotic interactions (e.g., soil moisture at the point of freezing determining the importance of physical stress on plant roots) deserves further investigation (Kreyling 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated export of a protein-like fraction, i.e., easily biodegradable DOM (Fellman et al, 2009), can be explained by less biotic demand and a domination of shallow flow paths during snowmelt bypassing large, strongly modified and aromatic DOM pools in the subsurface (Fellman et al, 2009). Also, near-surface freeze-thaw cycles during winter provide fresh DOM from microbial cell lysis and root mortality, which is not utilized due to the low productivity (Haei et al, 2012;Fellman et al, 2009). Differences between the two sites were more evident in other PARAFAC components.…”
Section: Snowmeltmentioning
confidence: 99%
“…The low winter temperatures can be a driver for winter preservation of organic matter in the catchment, through lowering of metabolic rates during cold winter months and lower flow rates on rivers and through soils. Additionally, Haei et al (2012) showed that bioavailability of DOM increased with increasing soil frost conditions in winter (i.e. lower winter temperatures lead to more labile DOM release from soils); this was attributed not directly to lowered metabolism during the winter but rather frost-induced destruction of fine root structures and cell lysis releasing labile organic matter upon thawing.…”
Section: Differences In Reactivity Between Rivers and Over Seasonsmentioning
confidence: 99%
“…Warmer mean winter temperatures, and reduced frost depth and duration (Haei et al, 2012) will lessen the preservation effect that is currently seen in the north. As the mean annual temperatures rise and become more like the southern catchments, it is likely that the overall reactivity of organic matter from the catchment will be lowered as well.…”
Section: Climate and Future Loadingsmentioning
confidence: 99%